2016
DOI: 10.1103/physrevx.6.021013
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Floquet-Anderson Insulator as a Nonadiabatic Quantized Charge Pump

Abstract: We show that two-dimensional periodically driven quantum systems with spatial disorder admit a unique topological phase, which we call the anomalous Floquet-Anderson insulator (AFAI). The AFAI is characterized by a quasienergy spectrum featuring chiral edge modes coexisting with a fully localized bulk. Such a spectrum is impossible for a time-independent, local Hamiltonian. These unique characteristics of the AFAI give rise to a new topologically protected nonequilibrium transport phenomenon: quantized, yet no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
378
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 327 publications
(387 citation statements)
references
References 66 publications
7
378
2
Order By: Relevance
“…1(a)]. Harnessing the unique properties of periodically driven quantum systems [12][13][14][15][16][17], here we show how these limitations can be circumvented: we find perfect spin-momentum locking in the stroboscopic dynamics of a periodically driven 1D lattice model. While conventional helical edge states require a time reversal symmetric topological 2D bulk [19], the spin-momentum locking in our 1D setting stems from topological properties in combined time-momentum (Floquet) space [see Fig.…”
mentioning
confidence: 75%
“…1(a)]. Harnessing the unique properties of periodically driven quantum systems [12][13][14][15][16][17], here we show how these limitations can be circumvented: we find perfect spin-momentum locking in the stroboscopic dynamics of a periodically driven 1D lattice model. While conventional helical edge states require a time reversal symmetric topological 2D bulk [19], the spin-momentum locking in our 1D setting stems from topological properties in combined time-momentum (Floquet) space [see Fig.…”
mentioning
confidence: 75%
“…Such lattices, which include coherent wave networks and periodically-driven lattices, are governed by evolution matrices rather than Hamiltonians. Previous studies have shown that Floquet lattice bandstructures can host a variety of phases, including topological insulator phases with protected surface states [11][12][13][14][15][16] . Most interestingly, there exist 2D "anomalous" Floquet insulator phases that are topologically distinct from conventional insulators, despite all bands having vanishing Chern numbers 14,15,17 ; this is unique to Floquet lattices, and cannot be understood in the framework of static Hamiltonians.…”
Section: Introductionmentioning
confidence: 99%
“…This approach does not rely on thermal equilibrium, and applies very naturally to time-dependent systems. It is therefore particularly suited for the identification of dynamical as well as Floquet phases [30][31][32][33][34][35][36][37][38][39].…”
mentioning
confidence: 99%